PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA BERBASIS REACT SEBAGAI IMPLEMENTASI K13 UNTUK MEMFASILITASI KEHETEROGENEN GAYA BELAJAR SISWA SMA/MA DI KOTA BANDAR LAMPUNG - Novi Ayu Kristiana Dewi; Bernadhita Herindri Samodera Utami (Jurnal Pendidikan Fisika, 2020)
The purpose of this research is to develop a learning tool. It is a physics module REACT based which can facilitate heterogeneity of student learning styles in class. The research method used is Research & Development (R&D) with four stages 4-D, namely define, design, develop, and disseminated. The results showed that the learning module developed was valid with good categories in the material component and very good in the media component. The application of the developed learning module was effective to improve student learning outcomes in the moderate category. The distribution of the module got a very good response from physics teachers.  Thus the learning device developed is feasible to use.